(untitled) (Research, Society and Development, 2021)
This work investigates the use of (Allium sativum L.) garlic peel extract, and (Theobroma L) cacao peel, as well as their synergy as a corrosion inhibitor for carbon steel in 0.5 mol.L-1 hydrochloric acid solution. The comparative study was performed in 1.11 g.L-1 of extract. The investigation was carried out using Fourier transform infrared spectroscopy (FTIR), electrochemical impedance spectroscopy (EIS), gravimetric techniques and scanning electron microscopy (SEM) as chemical, electrochemical and morphological characterization techniques, respectively. Gravimetric tests results showed a reduction in the corrosion rate of the extracts, with 90.7% efficiency for garlic extract and 89% for cacao extract, however, the mixture of the compounds presented an inhibition superior to 98%, showing the great synergism between the studied species. While the EIS results showed a higher impedance module value for cacao extract compared to garlic extract. Chemical analysis for extracts of garlic and cacao obtained by FTIR showed the presence of compounds based on sulfur and nitrogen, which are responsible for corrosion inhibiting effect. The SEM images obtained showed the formation of a film which reduces the evaluation of the corrosive process. Then, it is possible to conclude, that the carbon steel surface immersed in 0.5 mol.L-1 HCl solution with garlic peel extracts or cacao peel extracts or both, presents a corrosion inhibiting effect.